Bilinear Interpolation Image Scaling Processor for VLSI Architecure - Pawar Ashwini Dilip; K Rameshbabu; Kanase Prajakta Ashok; Shital Arjun Shivdas (Institute of Advanced Engineering and Science, 2014)
We introduce image scaling processor using VLSI technique. It consist of Bilinear interpolation, clamp filter and a sharpening spatial filter. Bilinear interpolation algorithm is popular due to its computational efficiency and image quality. But resultant image consist of blurring edges and aliasing artifacts after scaling. To reduce the blurring and aliasing artifacts sharpening spatial filter and clamp filters are used as pre-filter. These filters are realized by using T-model and inversed T-model convolution kernels. To reduce the memory buffer and computing resources for proposed image processor design two T-model or inversed T-model filters are combined into combined filter which requires only one line buffer memory. Also, to reduce hardware cost Reconfigurable calculation unit (RCU)is invented. The VLSI architecture in this work can achieve 280 MHz with 6.08-K gate counts, and its core area is 30 378 μm2 synthesized by a 0.13-μm CMOS process.